Human Immunodeficiency Virus Testing, Diagnosis, Linkage to Care, and Prevention Services Among Persons Who Inject Drugs, United States, 2012–2017. (2nd September 2020) - Rao, Shubha; Song, Wei; Mulatu, Mesfin S; Seena, Emilie; Essuon, Aba; Heitgerd, Janet
Abstract: Background: Human immunodeficiency virus (HIV) testing and early diagnosis is associated with effective disease management and reduction in HIV transmission among persons who inject drugs (PWID). We examined trends in HIV testing outcomes among PWID during 2012–2017. Methods: Centers for Disease Control and Prevention (CDC)-funded HIV testing data submitted by 61 health departments and 150 directly-funded community-based organizations during 2012–2017 were analyzed. We calculated estimated annual percentage changes (EAPC) to assess trends for HIV testing and testing outcomes. Results: A total of 19 739 857 CDC-funded HIV tests were conducted during 2012–2017. Of these, 529 349 (2.7%) were among PWID. The percentage of newly diagnosed HIV increased from .7% in 2012 to .8% in 2017 (EAPC, 4.15%). The percentage interviewed for partner services increased from 46.7% in 2012 to 66.3% in 2017 (EAPC, 1.81%). No significant change was identified in trends for linkage to HIV medical care ≤90 days after diagnosis (EAPC, 0.52%) or referral to HIV prevention services (EAPC, 0.98%). Conclusions: Human immunodeficiency virus testing data revealed an increasing trend in newly diagnosed HIV among PWID but not linkage to HIV medical care or referral to prevention services. Expanding efforts to increase HIV testing and enhance linkage to services can lead to reductions in HIV transmission and improved health outcomes.